Clonidine extended-release tablets for the treatment of ADHD. (April 2012) - Daughton, Joan; Corr, Lindsey; Liu, Howard; West, Madeline
SUMMARY  Treatment guidelines for ADHD recommend stimulants as a first-line therapy. However, as many as 15% of patients are unresponsive to these medications, while others are unable to tolerate stimulants. For some patients with ADHD, there is a clear need for nonstimulant therapies. This article aims to summarize the current evidence regarding the use of clonidine extended release (Kapvay™, Shionogi Pharma, GA, USA) in the treatment of children and adolescents with ADHD.